Integrative and Exclusionary Roles of Trust in Timber Value Chain in the Southern Highlands of Tanzania. Issue 1 (2nd January 2022) - Martin, Respikius
Abstract: Contract and trust are the two main governance mechanisms that influence actors' integration into value chains. Nevertheless, most studies treat trust as a complement to formal contract, paying less attention on the circumstances in which trust becomes a sole mechanism of governance. The aim of this article is to examine how trust shapes integration in the non-industrial timber value chain in the Southern Highlands of Tanzania. Timber, which is the pillar of the districts' revenue in the area, contributes significantly to the income of smallholder households. The study adopted an exploratory cross-sectional study design whereby data were collected mainly through in-depth interviews and focus group discussions with actors of the timber value chain. The findings showed that spot market and relational governance were the two main linkages in the timber value chain. Spot market linkage is characterized by absence or little trust, while some trust is present in relational linkage. In relational linkage, trust helps integration of actors in the value chain through enabling them access market information, capital in the form of credit, technology for processing timber, and coordination and collaboration among the actors. However, trust is associated with some challenges and to some actors, it plays an exclusionary role. The study recommends for the promotion of trust along with other social control mechanisms such as social knowledge in order to address these challenges.